The role of socioeconomic welfare in the prevalence of severe vitamin D deficiency, vitamin B12 deficiency and glucose metabolic changes in population of Karaj, Iran - Houshdar, Mahsa; Samimi Ardestani, Seyed Mehdi; Sadr, Seyed Saeed (International Journal of Applied Behavioral Sciences, 2015)
Introduction: Online Medicare is a method in which parts of a medical process, whether its diagnostics, monitoring or the treatment itself will be completed by using online services. At the first step the students were registered for using the system. They participated in estimating depression scale; anxiety scale and clinical interview by online medical care system. Subsequently, the lab examination tests were performed on persons specified by the system. The lab examinations include: serum level of vitamin D3&4, serum level of vitamin B125&6, fasting blood sugar7&8, HbA1c7&8, thyroid function test9&10 and CBC. All of the students were solely treated by vitamins or minerals therapy and/or treatment of medical problems (such as hypothyroidism). Methods: For detecting the role of socioeconomic welfare in the prevalence of the diseases, we implement the system in a low middle class boy’s state high school, and in an above average boy’s state high school and in an above average boy’s private high school. The prevalence of severe vitamin D deficiency, hypoglycemia, impaired fasting glucose level and vitamin B12 deficiency were compared in students who lay in different socioeconomic situation. Results: Severe vitamin D deficiency is significantly higher in above average neighborhoods than low middle class neighborhoods with p value = 0.024 < 0.05. Significant difference in vitamin B12 deficiency, hypoglycemia and impaired fasting glucose were seen in deferent high schools, but it is not related to socioeconomic situation. Conclusion: In Karaj, Iran, in societies with better socioeconomic situation, we can find higher severe vitamin D deficiency, it can be due to urbanization, living in apartment, over protection, preferring indoor games to outdoor games. Declaration of Interest: None.